“Trying to Get Out from under Water”: Paradox and Power in the Audit Senior Associate Role - Blum, Emily S.; Hoang, Kris (The Accounting Review, 2026)
ABSTRACT Audit senior associates are essential to audit production, yet we know little about how they experience their organizational role. We interview 45 U.S.-based audit seniors and find they experience persistent paradoxical tensions between contradictory yet interrelated objectives, stemming from their middle hierarchical position as both experienced associates and novice executives. Applying Paradox Theory, we find seniors sometimes work around paradox by attending to one paradoxical objective to temporarily alleviate tension but leave the other paradoxical objective neglected. Other times, seniors work through paradox by dynamically engaging with both paradoxical objectives, particularly when empowered by perceiving adequate resources—time, information, and social capital. Our study reconceptualizes seniors as self-directed fledgling leaders whose capabilities are forged through navigating paradoxical tensions, expanding the conventional academic view of seniors as experienced associates. We discuss how audit firm-level tensions revealed through seniors’ experiences offer insights for human capital development and audit quality.